Ekspresi Gerak Dinamis Olahraga dalam Karya Seni Patung Deformatif - Patdli Mulyadi; Lisa Widiarti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The purpose of this discussion is to examine the expression of dynamic sports movements in deformative sculpture. Humans naturally produce various movements that have aesthetic value, both consciously and unconsciously. These movements appear in static daily activities and in structured physical activities such as sports, which are classified as dynamic movements. Dynamic movements have patterns, rhythms, and intensities that create strong, harmonious, and meaningful body expressions. Sports provide physical benefits while displaying beauty through variations in tempo, space, energy, and time. In sports such as swimming, running, and pole vaulting, athletes' movements demonstrate a combination of muscle strength, body flexibility, and balance that create high visual aesthetics. The beauty of these movements inspires the creation of works of art, particularly in deformative sculpture. Deformative styles are used to express human body movements at certain moments in sports. This sculpture aims to convey that sports are not only physical activities, but also as an expression of the beauty of body movements that can be appreciated artistically. Through this work, the author hopes to demonstrate that sports as a visual art has aesthetic value that deserves to be appreciated and interpreted more deeply.